Support for marijuana legalization in the US state of Washington has continued to increase through 2016() - Subbaraman, Meenakshi Sabina (Drug Alcohol Depend, 2017)
BACKGROUND: Support for the legalization of recreational marijuana continues to increase across the United States and globally. In 2016, recreational marijuana was legalized in the most populous US state of California, as well as three other states. The primary aim of this study was to examine trends in support for recreational marijuana legalization in Washington, a state which has had legal recreational marijuana for almost four years, using data collected over the four years post-legalization. A secondary aim was to examine trends in support for the cultivation of marijuana for personal use. METHODS: Data come from geographically representative general population samples of adult (aged 18 and over) Washington residents collected over five timepoints (every six months) between January 2014 and April 2016 (N = 4,101). Random Digit Dial was used for recruitment. Statistical analyses involved bivariate comparisons of proportions across timepoints and subgroups (defined by age, gender, and marijuana user status), and multivariable logistic regression controlling for timepoint (time) to formally test for trend while controlling for demographic and substance use covariates. All analyses adjusted for probability of selection. RESULTS: Support for legalization in Washington has significantly increased: support was 64.0% (95% CI: 61.2%–67.8%) at timepoint 1 and 77.9% (95% CI: 73.2%–81.9%) at timepoint 5. With each six months’ passing, support increased 19% on average. We found no statistically significant change in support for home-growing. CONCLUSIONS: Support for marijuana legalization has continued to significantly increase in a state that has experienced the policy change for almost four years.